2017
DOI: 10.1111/tog.12343
|View full text |Cite
|
Sign up to set email alerts
|

Effect of obesity on assisted reproductive treatment outcomes and its management: a literature review

Abstract: Obesity is associated with infertility and poor obstetric outcomes. The current trends of advanced maternal age and rising obesity rates contribute indirectly to the growing demand for fertility treatment and assisted reproduction treatment (ART), posing clinical and ethical dilemmas for fertility service providers. The live-birth rate, after ART, is significantly lower in obese women than non-obese women, possibly due to impaired oocyte quality and/or defective endometrial receptivity. Poor ART outcomes corre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Since serum folate levels are inversely related to pre-pregnancy body mass [131], association findings would be expected, and do occur. Despite late macrosomia with obesity-related metabolic disturbances, there is excess growth restriction early on [132], as well as increases in limb reductions; anorectal, renal, and cardiovascular anomalies [133][134][135]; fertility issues [136]; prematurity; early losses and stillbirth; and possibly perinatal difficulties [137].…”
Section: Folate and Methylationmentioning
confidence: 99%
“…Since serum folate levels are inversely related to pre-pregnancy body mass [131], association findings would be expected, and do occur. Despite late macrosomia with obesity-related metabolic disturbances, there is excess growth restriction early on [132], as well as increases in limb reductions; anorectal, renal, and cardiovascular anomalies [133][134][135]; fertility issues [136]; prematurity; early losses and stillbirth; and possibly perinatal difficulties [137].…”
Section: Folate and Methylationmentioning
confidence: 99%
“…There is a lot of evidence that lifestyle factors can influence on ARTs outcomes [12, 13]. For example, studies have demonstrated that female age [14], smoking [15], weight [16], diet [17], exercise [18], psychological stress [19], caffeine consumption [20], alcohol consumption [20] and exposure to environmental pollutants [21] significantly decreases the chance of clinical pregnancy and live birth. Little has been done on the effects of male factors on the outcome of ARTs, and clinical observations in this field are small and contradictory.…”
Section: Introductionmentioning
confidence: 99%
“…Obesity is also present in 20–70% of women with PCOS, depending on geographic region ( Li et al, 2018 , Lim et al, 2012 , Pandey et al, 2010 , Silvestris et al, 2018 ). Obese women exhibit reduced fecundity, even after several ART treatment cycles ( Khairy and Rajkhowa, 2017 , MacKenna et al, 2017 ).…”
Section: Obesity and Infertilitymentioning
confidence: 99%